PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN KOSMETIK DAN KEPERLUAN RUMAH TANGGA SEBELUM DAN SAAT COVID-19 - Trisna Wulandari; Matdio Siahaan (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
The purpose of this study is to determine the financial performance of the cosmetics and household goods sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2020 period. In this study, financial performance is calculated by financial ratios consisting of liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The population in this study were 9 companies and the sample used was 8 companies with 2 years of observation. The data collection technique used for this research is a documentation technique whose sources come from the idx website and the official website of the company concerned. The data collection method used is literature study. And the analysis technique used in this research is descriptive statistics, normality test and hypothesis testing with Paired Sample T-Test and Wilcoxon Signed Rank Test. The results showed that simultaneously there was no significant difference in financial performance between the cosmetics and household goods sub-sector companies listed on the IDX before and during the COVID-19 pandemic seen from the liquidity ratio with the current ratio and quick ratio, solvency ratio with debt to assets ratio and debt to equity ratio, profitability ratio with net profit margin, return on assets and return on equity, as well as activity ratio with total assets turn over and working capital turn over.